Investigating HIV/AIDS in southern Africa: Webb, D (1997) HIV and AIDS In Africa. Cape Town: David Philip. ISBN 0 86486 341 1 - MacPhail, Catherine (PINS-Psychology in Society, 2026)
The development of effective and appropriate prevention programmes to limit the spread of HIV/AIDS in southern Africa depends on an understanding of the complex dynamics of the epidemic - an interaction between culture, individual action and sociopolitical factors in different times and places. Through the use of both social theory and a geographical perspective, Webb addresses a number of topics implicated in the spread of HIV/AIDS. What makes this attempt different is his in-depth consideration of a number of topics usually given only superficial explanation. In addition, Webb points to the fact that generalization across space is neither desirable nor useful when attempting to understand the HIV/AIDS epidemic and the book therefore, traces a number of topics through the perceptions and experiences of five southern African community field sites. The various sites locate AIDS in the geographical and social settings of migrancy, major road networks, racial suspicion and health seeking behaviour In the context of available health care options. In so doing, Webb provides possibilities for future avenues of research within other localized study areas.